2017
DOI: 10.1038/s41598-017-01836-8
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory Ca++-activated K+ channels are inhibited by hydroxychloroquine

Abstract: Antimalarials have demonstrated beneficial effects in Systemic Lupus Erithematosus and Rheumatoid Arthritis. However, the mechanisms and the molecular players targeted by these drugs remain obscure. Although hydroxychloroquine (HCQ) is a known ion channel inhibitor, this property has not been linked to its anti-inflammatory effects. We aimed to study whether HCQ inhibits pro-inflammatory ion channels. Electrophysiology experiments demonstrated that HCQ inhibited Ca++-activated K+ conductance in THP-1 macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…We recently showed that Ca 2+ -activated K + channels are involved in ATP-triggered inflammasome activation ( Schroeder et al., 2017 ). We therefore inhibited Ca 2+ -activated K + channels in ATP-treated WT and Tmem176b −/− BMDCs and determined the amounts of IL-1β in culture supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that Ca 2+ -activated K + channels are involved in ATP-triggered inflammasome activation ( Schroeder et al., 2017 ). We therefore inhibited Ca 2+ -activated K + channels in ATP-treated WT and Tmem176b −/− BMDCs and determined the amounts of IL-1β in culture supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxychloroquine sulfate and chloroquine can block internal TLR signaling and reduce the production of proinflammatory cytokines, and they have been widely used to treat autoimmune diseases like arthritis (73). Hydroxychloroquine can also inhibit proinflammatory Ca 2+ -activated K + channels, leading to impaired inflammasome activation (74). On the other hand, chloroquine has been shown to have significant anti-SARS-CoV-2 efficacy both in vivo and in vitro (75,76).…”
Section: Other Anti-inflammatory Treatmentsmentioning
confidence: 99%
“…masome activation in human and mouse macrophage and dendritic cells (25). BK channel blockers were able to suppress myelin phagocytosis of LPS-activated rat macrophages (26) and abrogate the elevations of some inflammatory biomarkers (chemokines and cytokines) in urine specimens of mice whose bladders were inoculated with LPS or uropathogenic E. coli (20).…”
Section: Bk Channel Modulates Neuroinflammationmentioning
confidence: 97%